The Effect of Organizational Safety Climate on Employees’ Psychological Capital and Job Satisfaction at the Tema Oil Refinery, Accra. - Humphrey, J. (University of Ghana, 2019)
This study investigated the extent to which employees’ perceived organizational safety climate predict their psychological capital and job satisfaction at the Tema Oil Refinery in Accra, using a survey research design. A total of 248 respondents were selected using Stratified random sampling technique. Questionnaires that contained the 50-item Occupational Safety Climate Questionnaire (NOSACQ-50) (Kines et al., 2011), 24-item Psychological Capital Questionnaire (Luthans, Avolio & Avey, 2007) and the 36-item Job Satisfaction Survey (Spector, 1997) were used to collect data. Data was analyzed with the Simple Linear Regression test and the PROCESS’’ Macro Script Moderation Analysis test within the Statistical Package for Social Sciences (SPSS) version 23 application software. Results showed that organizational safety climate predicts employees’ psychological capital and job satisfaction. Results also revealed that employees’ age and rank does not have a moderating effect on the relationship between organizational safety climate and job satisfaction. Finally, respondents’ age, rank and job tenure predicted organizational safety climate. It was concluded that organizational safety climate predict the psychological capital and job satisfaction of employees’ at the Tema Oil Refinery in Accra. Hence, positive organizational safety climate has a positive effect on employees’ psychological capital and job satisfaction whereas negative organizational safety climate has a negative effect on employees’ psychological capital and job satisfaction.
MPhil. Industrial and Organizational Psychology
Keywords: Psychosocial Safety Climate; Organizational Safety Climate; Job Satisfaction; Ghana; Tema Oil Refinery